Hydrogen bond organic framework material for flue gas desulfurization as well as preparation method and application of hydrogen bond organic framework material
Patent Information
- Application Number
- CN202411558505.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-04
Smart Images

Figure CN119431813A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flue gas desulfurization, and in particular to a hydrogen bond organic framework material, a preparation method thereof and application thereof in flue gas desulfurization. Background Art
[0002] Flue gas desulfurization is a key technology used to reduce the sulfur dioxide (SO2) content in industrial flue gas. Sulfur dioxide is one of the main pollutants produced when burning fuels such as coal, which has serious impacts on the environment and human health. In order to reduce sulfur dioxide emissions, flue gas desulfurization technology is widely used in industrial fields such as power plants, steel mills and chemical plants. The flue gas desulfurization process plays a key role in the industrial and energy fields. With the acceleration of industrialization and the growth of energy demand, sulfur dioxide released by the burning of fossil fuels has become one of the important sources of environmental pollution. This gas not only harms human health, but also has an impact on the atmospheric environment, natural ecology and buildings that cannot be ignored.
[0003] The emergence and development of flue gas desulfurization technology fills an important gap in environmental protection. By utilizing various desulfurization technologies, sulfur dioxide can be effectively removed from flue gas to reduce its harm to the environment. This not only complies with international environmental protection standards, but is also a necessary measure to protect public health and promote sustainable development.
[0004] At present, the methods of flue gas desulfurization mainly include wet desulfurization and dry desulfurization. Wet desulfurization: lime-gypsum method (common method), spray lime slurry into flue gas, sulfur dioxide reacts with lime to form calcium sulfide, and finally forms gypsum precipitation. This method can remove sulfur dioxide efficiently, but it requires the treatment of gypsum waste. Lime-emulsion method, suspend lime in emulsion to form fine particles, increase the contact area between lime and sulfur dioxide in flue gas, and improve desulfurization efficiency. Lime-double alkali method, combined with lime and other alkaline substances (such as sodium alkali or soda ash) to enhance the desulfurization effect. Dry desulfurization: activated carbon adsorption method, using activated carbon to adsorb sulfur dioxide in flue gas, and then regenerating the saturated activated carbon for reuse. Dry reactor method, using fixed bed or moving bed reactor, removes sulfur dioxide from flue gas through fixed adsorbents (such as calcium oxide, sodium oxide).
[0005] Hydrogen-bonded organic framework materials are a new type of porous materials with the following characteristics: Hydrogen bond construction. The construction of hydrogen-bonded organic framework materials depends on hydrogen bonding, and is usually a network structure formed by connecting organic molecules through hydrogen bonds. This moderately strong hydrogen bond interaction gives the material good structural stability and controllability. Porous properties. Hydrogen-bonded organic framework materials have rich pore structures, which can be used for adsorption and storage of gas molecules, catalytic reactions, etc. The pore size, shape and distribution can be regulated by rationally designing the structure of organic molecules to meet different application requirements. Adjustability and controllability. Since hydrogen-bonded organic framework materials are formed by self-assembly of hydrogen bonds of organic molecules, the properties of the material can be regulated by the structure of synthetic organic molecules. This adjustability and controllability give it a wider range of application potential. Selective adsorption performance. Since the design of the pores can be optimized for specific molecules or molecular size ranges, hydrogen-bonded organic framework materials often show high selective adsorption capacity for specific gases or solvents, and can be used in gas separation, energy storage and other fields. Environmentally friendly and sustainable, hydrogen-bonded organic framework materials are usually composed of natural or synthetic organic molecules. Their synthesis methods are relatively environmentally friendly and can be sustainably utilized through reuse and regeneration. Due to their unique structural characteristics and diverse application potential, hydrogen-bonded organic framework materials have shown broad application prospects in the fields of gas adsorption, separation, catalysis, drug release and energy storage, and are attracting more and more attention and research from scientists and engineers. How to prepare hydrogen-bonded organic framework materials with good stability, high sulfur dioxide adsorption capacity and high sulfur dioxide / carbon dioxide adsorption and separation selectivity at low cost is a challenging technical problem. Summary of the invention
[0006] In further research on the activated microcrystals (organic soft porous framework materials) prepared in the Chinese invention patent CN114907230, it was found that the material showed specific adsorption to acetylene, but almost no adsorption to several other common gases. In order to overcome the problems of poor selectivity of current industrial separation of sulfur dioxide / carbon dioxide, complex material preparation, and high cost, the present invention uses the method of carbon dioxide-induced hydrogen-bonded organic framework materials to complete the preparation of hydrogen-bonded organic framework materials in two steps. The obtained hydrogen-bonded organic framework materials have the characteristics of ultra-high stability, high sulfur dioxide / carbon dioxide adsorption selectivity, simple preparation, high cycle stability, and recyclability.
[0007] Based on the above technical concept, the present invention is based on the activated microcrystals (organic soft porous framework material) prepared in patent CN114907230, and achieves the purpose of the present invention through the following technical scheme.
[0008] The technical solution adopted by the present invention is: under the condition of minus 87°C to minus 20°C, the activated microcrystals (organic soft porous framework material) prepared in patent CN114907230 are placed in a carbon dioxide atmosphere at one atmosphere of pressure and left to stand for 6-12 hours, and then vacuumed with a vacuum pump for 1-2 hours to remove the carbon dioxide molecules, thereby obtaining the hydrogen bonded organic framework material.
[0009] Further, a preferred preparation method of the present invention is:
[0010] (1) The activated crystalline powder was placed in a carbon dioxide atmosphere at -20°C for 6 hours.
[0011] (2) Using a vacuum pump to evacuate for 1 hour, the purpose is to remove the carbon dioxide molecules and obtain the hydrogen bond organic framework material.
[0012] (3) The material after gas adsorption can be regenerated through steps (1) (2).
[0013] The organic soft porous framework material of the present invention has the following structural formula:
[0014]
[0015] Furthermore, the present invention provides the use of the obtained hydrogen-bonded organic framework material for flue gas desulfurization, and the hydrogen-bonded organic framework material can be used for adsorption of sulfur dioxide in flue gas.
[0016] Furthermore, the adsorption capacity of sulfur dioxide by this material at 25°C and 1 bar reached 151 cm 3 / g.
[0017] The technical effect of the present invention is that the preparation of a hydrogen-bonded organic framework material for flue gas desulfurization can be achieved by adjusting and changing the technical means in the present invention, and the obtained hydrogen-bonded organic framework material has the following characteristics:
[0018] (1) The hydrogen-bonded organic framework material prepared by this method exhibits specific adsorption for sulfur dioxide, but has almost no adsorption for other components in flue gas such as carbon dioxide, nitrogen, and methane.
[0019] (2) Since the material itself has good hydrophobicity, the amount of water adsorbed is extremely low, which greatly reduces the impact of water vapor on the adsorption capacity of the material in the real flue gas environment.
[0020] (3) The penetration test of the material in a simulated real flue gas environment shows that the prepared material has a good separation effect on sulfur dioxide and carbon dioxide.
[0021] (4) The material exhibits ultra-high water stability and acid-base stability, which is conducive to its application in real flue gas environments.
[0022] (5) The material still maintains a good structure after multiple adsorption / desorption cycles, indicating its high cyclic stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a schematic diagram of the preparation process of the hydrogen-bonded organic framework material of the present invention.
[0024] Figure 2 This is the single crystal structure of the hydrogen bond organic framework material obtained by the present invention.
[0025] Figure 3 This is the single-component adsorption curve of different gases at 25°C of the present invention.
[0026] Figure 4 This is the sulfur dioxide / carbon dioxide selectivity calculation for the present invention.
[0027] Figure 5 This is the water adsorption / desorption isotherm at 25°C of the present invention.
[0028] Figure 6 This is the single crystal to single crystal transformation after the hydrogen bond organic framework of the present invention adsorbs sulfur dioxide.
[0029] Figure 7 This is a water stability test of the present invention, powder X-ray diffraction pattern.
[0030] Figure 8 This is the experimental curve of the simulated flue gas components (dry) penetrating the column at 25°C of the present invention.
[0031] Fig. 9 This is the experimental curve of simulating real flue gas components (humid) penetrating the column at 25°C of the present invention. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further illustrated by the following embodiments.
[0033] Example 1
[0034] Preparation of hydrogen bond organic framework materials. The preparation process is shown in the attached Figure 1 The method for preparing hydrogen bonded organic framework material microcrystals is to expose the activated microcrystals to a CO2 atmosphere of about 1 bar and 195K for 12 hours, and then perform a vacuum treatment for 2 hours to finally obtain hydrogen bonded organic framework microcrystals (HOF-NKU-1). The structure of the material is shown in the attached figure. Figure 2 shown.
[0035] Single component gas adsorption-desorption experiment
[0036] See attached Figure 3 In order to test the adsorption and separation performance of the above synthesized hydrogen-bonded organic framework material, the single-component adsorption isotherms of sulfur dioxide, carbon dioxide, nitrogen, oxygen, and methane were carried out using the above hydrogen-bonded organic framework material as an adsorbent. 180 mg of adsorbent was taken and the adsorption temperature was set to 25 degrees. After testing, at 25°C and 1 bar, the adsorption amount of sulfur dioxide reached 151 cm 3 / g, the adsorption capacity of carbon dioxide is only 15cm 3 / g.
[0037] Example 2
[0038] See attached Figure 4 In order to test the adsorption selectivity of the hydrogen-bonded organic framework materials synthesized above, the adsorption data were used to calculate the sulfur dioxide / carbon dioxide selectivity.
[0039] Example 3
[0040] See attached Figure 5 In order to test the water adsorption capacity of the above synthesized hydrogen-bonded organic framework material, the single component adsorption / desorption isotherm of water vapor was carried out using the above adsorbent. 210 mg of adsorbent was taken and the adsorption temperature was set to 25 degrees. At 25°C and 1 bar, the water adsorption amount reached only 17 mg / g, which has a very low water adsorption amount.
[0041] Example 4
[0042] See attached Figure 6 In order to study the mechanism of sulfur dioxide adsorption by the above-synthesized hydrogen-bonded organic framework material, the crystal was taken out from the scintillation bottle and placed in the air to allow the dichloromethane to evaporate slowly. After standing for 24 hours, the single crystal was analyzed to obtain the activated single crystal data. A part of the activated single crystal was placed in a sulfur dioxide atmosphere for 6 hours and the single crystal structure was analyzed. From the single crystal data, it can be seen that it has a transition from single crystal to single crystal and then to single crystal.
[0043] Example 5
[0044] See attached Figure 7 In order to test the stability of the hydrogen-bonded organic framework material synthesized above, the hydrogen-bonded organic framework material prepared above was placed in water, 12M NaOH solution, 12M HCl solution, and air for two weeks, and its powder XRD was tested. It was observed that its structure did not change and had good stability.
[0045] Example 6
[0046] See attached Figure 8In this embodiment, 1.0224 grams of HOF-NKU-1 was loaded into a quartz tube with an inner diameter of 6 mm. Before the adsorption test, the sample was activated at 298K for 6 hours by helium (He) flowing at a rate of 20mL / min to ensure the removal of any impurities. The gas mixture used in the adsorption process consisted of SO2, CO2, O2 and N2, with a volume ratio of 0.3:15:3.5:81.2 and a concentration of 3000ppm. After a two-hour gas preparation phase, this mixed gas was introduced into the tube, and the wet path carrier gas was fully mixed with the SO2, CO2, O2 and N2 gases. The outlet gas effluent of the adsorption bed was continuously monitored by a gas analysis mass spectrometer. The test curve was obtained by the software. After testing, the separation effect of SO2, CO2, O2 and N2 was obvious.
[0047] Example 7
[0048] See attached Fig. 9 In order to test the actual separation effect of this type of hydrogen-bonded organic framework material on flue gas, the above-synthesized adsorbent was used to pre-saturate a column filled with HOF-NKU-1 by flowing a helium gas stream containing 3% H2O at a rate of 20 mL / min until a breakthrough occurred. A penetration test of a SO2 / CO2 / N2 / O2 mixed gas was carried out under humidity conditions. In this example, 1.0224 grams of HOF-NKU-1 was loaded into a quartz tube with an inner diameter of 6 mm. Before the adsorption test, the sample was activated at 298K for 6 hours by flowing helium (He) at a rate of 20 mL / min to ensure the removal of any impurities. The gas mixture used in the adsorption process consisted of SO2, CO2, O2 and N2, with a volume ratio of 0.3:15:3.5:81.2 and a concentration of 3000 ppm. After a two-hour gas preparation phase, this mixed gas was introduced into the tube, and the wet path carrier gas was fully mixed with the SO2, CO2, O2 and N2 gases. The outlet gas effluent of the adsorption bed is continuously monitored by a gas analysis mass spectrometer. The test curve is obtained by the software. After testing, the separation effect of SO2, CO2, O2 and N2 is obvious.
[0049] Example 8
[0050] Different from Example 1, the preparation method of the microcrystals in this example is to expose the activated microcrystals to a CO2 atmosphere of about 1 bar and 253K for 6 hours, and then perform a vacuum treatment for 1 hour, and finally obtain hydrogen-bonded organic framework microcrystals.
[0051] Example 9
[0052] Different from Example 1 and Example 8, the method for preparing the microcrystals in this example is to expose the activated microcrystals to a CO2 atmosphere of about 1 bar and 220K for 8 hours, and then perform a vacuum treatment for 1 hour to finally obtain hydrogen-bonded organic framework microcrystals.
[0053] Based on the above embodiments, the present invention is as follows Figure 1 As shown, the organic soft porous framework material obtained by the patent CN114907230 is placed in a carbon dioxide atmosphere at an atmospheric pressure for a certain period of time, and then vacuumed with a vacuum pump to obtain the hydrogen-bonded organic framework material. Further, the present invention verifies the single-component adsorption of sulfur dioxide, carbon dioxide, nitrogen, oxygen, and methane on the obtained hydrogen-bonded organic framework material, and tests the actual separation effect of this type of hydrogen-bonded organic framework material on flue gas. The experimental results show that the material obtained by the present invention exhibits specific adsorption of sulfur dioxide, while other components in flue gas such as carbon dioxide, nitrogen, and methane are almost non-adsorbed. In the penetration experiment simulating the real flue gas environment, it can be seen that the prepared material has a good separation effect on sulfur dioxide and carbon dioxide. In the performance test of the hydrogen-bonded organic framework material obtained by the present invention, it is verified that the material itself has good hydrophobicity, and based on this characteristic, the adsorption performance of sulfur dioxide in flue gas in the flue environment can also be greatly improved. And the material still maintains a good structure after multiple adsorption / desorption, has strong water stability and acid-base stability, which is conducive to the application in the real flue gas environment.
Claims
1. A method for preparing a hydrogen-bonded organic framework material for flue gas desulfurization, characterized in that: The organic soft porous framework material is placed in a carbon dioxide atmosphere at an atmospheric pressure and allowed to stand for a certain period of time, and then evacuated with a vacuum pump to obtain the hydrogen bond organic framework material. The organic soft porous framework material has the structural formula:
2. The method for preparing a hydrogen-bonded organic framework material for flue gas desulfurization according to claim 1, characterized in that: The organic soft porous framework material is prepared by placing activated crystalline powder in a carbon dioxide atmosphere at -87°C to -20°C for 6-12 hours.
3. The method for preparing a hydrogen-bonded organic framework material for flue gas desulfurization according to claim 1, characterized in that: The vacuum is drawn with a vacuum pump for 1-2 hours to remove the carbon dioxide molecules and obtain the hydrogen bond organic framework material.
4. A hydrogen-bonded organic framework material for flue gas desulfurization, characterized in that: It is prepared by the method according to any one of claims 1 to 3.
5. The use of the hydrogen-bonded organic framework material for flue gas desulfurization according to claim 4, characterized in that: Used for the adsorption of sulfur dioxide in flue gas.
6. The use of the hydrogen-bonded organic framework material for flue gas desulfurization according to claim 5, characterized in that: The material can adsorb sulfur dioxide up to 151 cm at 25°C and 1 bar. 3 / g.
Citation Information
Patent Citations
Carbon dioxide induced nanopore hydrogen bond organic framework material as well as preparation method and application thereof
CN114262444A
Organic soft porous framework material as well as preparation method and application thereof
CN114907230A
Thermo-sensitive organic light-emitting molecule, organic light-emitting molecule-doped film, and preparation method and application of thermo-sensitive organic light-emitting molecule-doped film
CN116768752A
Dihydrogen bond organic framework material with porous structure as well as preparation method and application of dihydrogen bond organic framework material
CN117903450A
Hydrogen bond organic framework nanocomposite material, and preparation method therefor and use thereof
WO2024082366A1
Cited By
A rare earth upconversion nanocrystal particle-hydrogen bond organic framework composite material and a preparation method thereof
CN119875640B